2022
DOI: 10.3389/fvets.2022.873460
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Whole Blood Taurine Concentrations in Dogs May Not Be Sensitive Indicators of Taurine Deficiency When Dietary Sulfur Amino Acid Content Is Reduced

Abstract: BackgroundTaurine status is impacted by dietary supply of methionine and cysteine (SAA) and possibly intestinal microbial activity, where plasma and whole blood taurine concentrations are currently used to evaluate taurine status.ObjectiveWe determined effects of dietary SAA restriction on rate and extent of taurine depletion of blood and skeletal muscle in dogs of two body sizes, and whether oral antibiotic administration affected the taurine depletion and fecal bile acid excretion of the dogs.MethodsAdult, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…The fact that none of the dogs measured had taurine deficiency argues against taurine deficiency playing a primary role in the current episode of diet-associated DCM, but further investigation is needed given the limited percentage of dogs in this study in which taurine was evaluated. In addition, a recent study 22 showed that whole blood taurine concentrations (and, in some dogs, plasma concentrations) may not be a sensitive measure of skeletal muscle depletion, and other measures of taurine status may be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that none of the dogs measured had taurine deficiency argues against taurine deficiency playing a primary role in the current episode of diet-associated DCM, but further investigation is needed given the limited percentage of dogs in this study in which taurine was evaluated. In addition, a recent study 22 showed that whole blood taurine concentrations (and, in some dogs, plasma concentrations) may not be a sensitive measure of skeletal muscle depletion, and other measures of taurine status may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases (n = 84) were from the US, with 18 states represented; cases were also submitted from Canada (6) and Germany (1). All DCM cases were diagnosed between January 2015 and August 31, 2022, as follows: 2015 (n = 1), 2016 (0), 2017 (2), 2018 (10), 2019 (22), 2020 (20), 2021 (21), and 2022 (through August 31; 15). At the time of DCM diagnosis, 76 dogs were eating commercial diets, 1 dog was eating a homemade diet, and diet was unknown or there was insufficient information available to determine whether the diet was nontraditional or traditional in 14 dogs (Figure 1).…”
Section: Dcm Groupmentioning
confidence: 99%
“…Most breeds of dogs can synthesize sufficient taurine when fed a methionine- and cysteine-adequate diet [ 43 ]. However, an inadequate intake of methionine and cysteine in diets [e.g., plant (e.g., peas, lentils, and rice)-based foods with no or insufficient taurine] may contribute to the development of dilated cardiomyopathy characterized by thin heart muscle and enlarged chambers in some breeds of dogs [ 98 , 99 ]. For example, a small proportion (1.3%–2.5%) of Newfoundland dogs fed commercially available diets that were considered to be complete and balanced in nutrition have a deficiency of taurine [ 100 ] due to reduced taurine synthesis possibly as a result of gene mutations [ 101 ].…”
Section: Metabolism Of Aas By Cats and Dogsmentioning
confidence: 99%
“…Only in the breeds of dogs that possess sufficient enzymes for taurine synthesis can the adequate provision of methionine plus cysteine in their diets prevent metabolic diseases such as dilated cardiomyopathy. Although concentrations of taurine in plasma and skeletal muscle reflect its availability in these animals, those in the whole blood may not be a sensitive indictor of taurine depletion caused by a low intake of bioavailable sulfur AAs in dogs, especially in large dogs [ 99 ].…”
Section: Metabolism Of Aas By Cats and Dogsmentioning
confidence: 99%
See 1 more Smart Citation